OHVIRA syndrome and its incomplete variant: multimodality imaging insights from two distinct presentations of Müllerian-renal anomalies - Pavuluri, Viharika; B. S., Pavan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Mullerian anomalies such as obstructed hemivagina and ipsilateral renal anomaly (OHVIRA) syndrome pose diagnostic challenges due to their embryological variability and diverse clinical presentations. We present two adult cases highlighting the spectrum of OHVIRA. The first case involved a 27-year-old female with primary infertility, where imaging revealed classical OHVIRA features including uterine didelphys, obstructed hemivagina with hematocolpos, and ipsilateral renal agenesis. The second case was a 19-year-old female with vague abdominal pain and no significant menstrual complaints, in whom magnetic resonance imaging (MRI) demonstrated uterine didelphys, a single cervix, and ipsilateral renal agenesis without obstruction an incomplete variant of OHVIRA. MRI was pivotal in both cases for accurate diagnosis and surgical decision-making. Early recognition of both complete and incomplete OHVIRA variants is essential to prevent complications such as infertility, endometriosis, and chronic pelvic pain. MRI remains the gold standard for anatomical evaluation, enabling timely diagnosis and optimal clinical management.